The Effect of Governance Accounting Mechanisms in Libyan Banks in Reducing Financial and Administrative Corruption (Abhat Journal, 2024)
This study aimed to investigate the role of governance in combating administrative and financial corruption. To examine this role, the study utilized global governance indicators developed by the World Bank in 1996, including the "Participation and Accountability Index," the "Political Stability and Absence of Violence Index," and the "Control of Corruption Index." The study focused on the Gulf Arab Company community, with the study sample comprising senior management, department managers, office managers, department heads, and internal auditors in the Gulf Arab Company.     To achieve the study's objectives, a descriptive-analytical approach was adopted, and a questionnaire was used as a data collection tool, distributed among the study sample. The study revealed several results, including the significant role of governance in combating administrative and financial corruption. The results also showed that political stability, absence of violence, and the rule of law are crucial factors in reducing corruption. The study recommended that governance in sector institutions should stem from a comprehensive vision of political decision-making and emphasized the necessity of awareness programs for employees and citizens regarding the importance of governance in combating corruption. This recommendation is particularly relevant as Libya is still in a phase of reconstruction, facilitating the integration of governance concepts within the country.
Keywords: financial corruption; Arab Gulf Company; Governance; World Bank